Clinical presentation and long-term outcome of patients with KCNJ11/ABCC8 variants: Neonatal diabetes or MODY in the DPV registry from Germany and Austria - Warncke, Katharina; Eckert, Alexander; Kapellen, Thomas; Kummer, Sebastian; Raile, Klemens; Dunstheimer, Desiree; Grulich-Henn, Jurgen; Wölfle, Joachim; Wenzel, Sandra; Hofer, Sabine E.; Dost, Axel; Holl, Reinhard W. (Pediatric Diabetes, 2022)
Objective: To describe clinical presentation/longterm outcomes of patients with ABCC8/KCNJ11 variants in a large cohort of patients with diabetes. Research Design and Methods We analyzed patients in the Diabetes Prospective Follow-up (DPV) registry with diabetes and pathogenic variants in the ABCC8/KCNJ11 genes. For patients with available data at three specific time-points-classification as K+-channel variant, 2-year follow-up and most recent visit-the longitudinal course was evaluated in addition to the cross-sectional examination.
CRIS-Team WoS Importer:2022-08-05